(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
In our day to day clinical practice we come across a lot of patients suffering from occlusal parafunctional habits or bruxism. Bruxism can be described as nonfunctional abnormal, involuntary contact of teeth, if ignored it leads to occlusal trauma. So for correct diagnosis and treatment a multidisciplinary approach was required in which dentists, psychiatrists, neurologists and physiotherapists play an important role. Causes for bruxism were multifactorial and the treatment modalities were also various. Bruxism can be a major concern for the dentist as they were required to not only diagnose but also intervene in most of the cases of bruxism. And if untreated it leads to destruction of dentition, muscle fatigue & temporomandibular pain. This article discusses the history of the current concepts in the diagnosis and treatment of bruxism.